The determinants of loan loss provision: study in local commercial banks in Malaysia / Siti Nadhirah Zabidi - Zabidi, Siti Nadhirah (2016)
This paper studies the determinants of loan loss provision on local commercial banks in Malaysia by using secondary panel data from Thomson one for 2005 until 2014. The sample of this study include of 8 commercial banks that listed in Bank Negara. The methodology used for this study is normality test, descriptive statistics, correlation test and multiple linear regression analysis. The variables that have been selected are total asset, total loan, earning before tax and equity ratio. The study is to investigate the factors ofthe determinants of loan loss provision and to determine the relationship between the determinants ofloan loss provision. After running the data, it is found that total asset (TA), earning before tax (EBT) and equity ratio (ER) are significant on loan loss provision.